Analysis of Prespect on Buddykuofficial Instagram Comments about Teddy Minahasa - Syakinah Melinda Harahap; Yusni Khairul Amri (LingLit Journal Scientific Journal for Linguistics and Literature, 2023)
One of the media used in sharing news is Instagram. In Instagram media there is a comment column for the public to freely comment on the news being shared. Within these comments there are several types of presuppositions. That way the author wants to do an analysis to describe the types of presuppositions contained in the comments on the upload of the official Buddyku Instagram account on October 19, 2022 about the news about Teddy Minahasa. The amount of data is 20 sentences of Instagram comments that are screenshots that are transcribed. The data in this study were analyzed based on George Yule's presupposition theory which divides presuppositions into 6 types of presuppositions. The results showed that of the 6 types of presuppositions according to George Yule, only 5 types of presuppositions were found in the comments on the Buddykuoffficial Instagram account upload on 19 October 2022 about the Teddy Minahasa news, namely existential presuppositions, factual presuppositions, lexical presuppositions, structural presuppositions, and counterfactual presuppositions. The most common type of presupposition is structural presupposition which is indicated by the form of interrogative sentences. Thus it is concluded that in expressing a comment on news uploads from the Buddykuofficial Instagram account, many people use a type of structural presupposition with the intention of the comment writer stating a fact with a question sentence. The fact is that police officers and lawyers in Indonesia cannot be trusted.